Evaluation of bioprospective potentialities of hyllosphere Microbial diversity & effect of electromagnetic Irradiation stress on their survival – a review - PRANAB GIRI (International Journal of Pharma and Bio Sciences, 2017)
Terrestrial vascular land plants have two system in their sporophyte such as the aerial foliar system and underground rhizoidal system; the former is called phyllosphere and the latter is called rhizosphere and the two systems altogether constitute phytosphere. Out of the two systems phyllosphere is more prone to microbial colonization since it has more exposure to atmosphere than to rhizosphere. The Phyllosphere system of plant is a novel ecological niche which executes a broad spectrum of microenvironment depending upon the plant species and such variation is accounting for a wide diversity of microorganisms. The inhabitant microbial population on phyllosphere plays immense role for plant protection and several aspects of benefits could be obtained from such colonizer which could be exploited not only for enhancement of crop productivity but also for their adaptability against adverse environment. The present article deals with the survey on the microbial diversity in the phyllosphere with the objective to explore the correlation of such diversity in bioprospective potentialities. Such valuable microbial wealth now a days are in jeopardy because of their relentless exposure to electromagnetic radiations coming out from different sources as consequence of modernization of the civilization as a cascading effect of electronic revolution. In this article emphasis is therefore given to search what strategies have so far been adopted to protect phyllosphere microbial wealth from the stress induced by electromagnetic irradiation (EMI). Possible models have been highlighted to design research methodologies in future to combat the hazards against beneficial microbes in an attempt to restore sustainable development and well being of mankind as a blessing of microbial population.